Estudos morfológicos e moleculares em populações de Piabina Reinhardt (Characidae, Stevardiinae) das bacias do alto rio Paraná e rio São Francisco, incluindo a descrição de uma nova espécie. - Cardoso, Lilian Queli Ferreira (2011)
Species of Piabina Reinhardt (1867) from the upper rio Paraná and rio São Francisco basins were molecularly characterized by the cytochrome c oxidase subunit I (COI) sequence and were taxonomic and phylogenetically analyzed. Molecular analysis resulted in the formation of three distinct clades: clade A (Piabina anhembi, rio Tietê basin), clade B (Piabina argentea, rio São Francisco and upper rio Paraná basins) and clade C (Piabina sp n., upper rio Paraná). Populations of P. argentea from the upper rio Paraná and rio São Francisco basins shared the same haplotype. Piabina anhembi, an endemic species from the rio Tietê headwaters presented distinct haplotype from the others, however, as only one individual was sequenced, intraspecific polymorphism was not analyzed. A new species of Pirapó and Pitangui rivers, upper rio Paraná basin, was discovered. The new species, herein described, showed wide intra-specific polymorphism, observed by the formation of nine haplotypes in the studied population. The interspecific genetic distances ranged from 3.0 to 6.7% and 6.7% between Piabina sp. n. and P. anhembi with P. argentea, and 3.0% between P. anhembi and P. argentea. Phylogenetic analysis showed that Piabina sp. n. has two synapomorphies consistent with the hypothesis of the genus monophyletism. Most of the 57 analyzed characters are in the same state as P. argentea and P.anhembi. The characters: 19 (anguloarticular horizontally shortened), 29 (anterior portion of the laterosensorial canal in the first infraorbital reaching or extending beyond the edge of the main body of the ossification), 30 (posterior portion of the first infraorbital overlapping the anterior portion the second infraorbital), 34 (third infrafaringobranquial teeth present) and 55 (presence of two epurals) were divergent. The new species described herein can be easily distinguished from its congeners by the combination of the following characters: anterior tooth of the triad partially inserted between the first and second teeth of the first series (vs. anterior tooth of the triad not inserted into the space between the first and second teeth of the first series), largest percentage of the distance from the dorsal-fin origin to the anal-fin origin in relation to standard length (vs. 31.1-35.3, 26,6-28,9 and 24,7-32,8), higher percentage of the distance between the dorsal-fin origin to the pelvic-fin origin (29.3-33.9, vs. 23,3-25,7 and 24,3- 30,8) and lower lobe of caudal fin more strongly blackish than that upper lobe (vs. lobes with the same coloration).